Characteristics and freezability of Gir bull semen - SONAR, B P; TIWARI, R P; POYAM, M R; MISHRA, G K; PANDEY, A K; NAIR, A K; SAHASRABUDHE, S A (The Indian Journal of Animal Sciences, 2016)
The present research was undertaken to study the characteristics of fresh and cryo-preserved semen of elite pure breed Gir (Bos indicus) bulls. The mean values of fresh seminal parameters in neat semen viz. seminal volume (ml), sperm concentration (millions/ml), progressive sperm motility (%), live sperm (%), intact acrosome (%), total morphological sperm abnormalities (%), hypo osmotic swelling (HOS %) and sperm penetration distance (SPD- mm) were 4.99 ± 0.26, 895.33 ± 82.68, 69.10 ± 0.75, 72.16 ± 0.64, 84.42 ± 0.77, 15.96 ± 0.44, 60.12 ± 1.19 and 31.32 ± 0.70, respectively. Sperm concentration, individual motility, live sperm, total sperm abnormalities and sperm penetration distance differed significantly between bulls. The semen was extended, filled and sealed in 0.25 ml straws maintaining 20 million spermatozoa/straw and cryo-preserved using programmable bio freezer (IMV). Cryo-preserved semen was assessed 24 h after freezing and immediately after thawing. Freezing significantly lowered progressive sperm motility (69.10 ± 0.75 vs 53.81 ± 0.61), intact acrosome (84.42 ± 0.77 vs 75.69 ± 1.10), HOST (60.12 ± 1.19 vs 55.71 ±1.33) and CMPT (31.32 ± 0.70 vs 27.97 ±0.72). Whereas, significantly higher percentages of sperm abnormalities (15.96 ± 0.44 vs 16.92 ± 0.57) were observed after freezing.